2019
DOI: 10.14393/dl37-v13n1a2019-17
|View full text |Cite
|
Sign up to set email alerts
|

Result linking adverbials in learner corpora

Abstract: This article aims to present an investigation of the use of the following linking adverbials: so, therefore, and thus in essay writing of Brazilian university students. Few corpora-based studies have been carried out on the use of cohesive devices in the written production of Brazilian university students in comparison to the writing of American and British university students. It is worth mentioning Matte and Sarmento (2018) and Dutra et al. (2017) who identified differences among the groups concerning the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Despite the fact that these investigations dealt with diff erent conjunctions [Dutra et al (2017) addition words (besides and also), Dutra et al (2019) result markers (thus, so and therefore) and Santos (2018) contrasting connectors (but and however)], they all detected either substantial quantitative diff erences (underuse or overuse as compared to LOCNESS or MICUSP), sentence position disparities, as well as discourse function inadequacies on the part of the learners. For instance, the marker so is used three times more in CorIFA than in LOCNESS, assuming beginning sentence functions of initiating a topic or announcing that an idea is going to be presented again (DUTRA et al, 2019), which have been attested as oral discourse markers (Carter & McCarthy, 2006). An interpretation shared by the three CorIFA investigations based on learners' overuse of conjunctions in sentence initial position is that register awareness needs to be better addressed in the Brazilian university context.…”
Section: Studies Based On Corifamentioning
confidence: 93%
“…Despite the fact that these investigations dealt with diff erent conjunctions [Dutra et al (2017) addition words (besides and also), Dutra et al (2019) result markers (thus, so and therefore) and Santos (2018) contrasting connectors (but and however)], they all detected either substantial quantitative diff erences (underuse or overuse as compared to LOCNESS or MICUSP), sentence position disparities, as well as discourse function inadequacies on the part of the learners. For instance, the marker so is used three times more in CorIFA than in LOCNESS, assuming beginning sentence functions of initiating a topic or announcing that an idea is going to be presented again (DUTRA et al, 2019), which have been attested as oral discourse markers (Carter & McCarthy, 2006). An interpretation shared by the three CorIFA investigations based on learners' overuse of conjunctions in sentence initial position is that register awareness needs to be better addressed in the Brazilian university context.…”
Section: Studies Based On Corifamentioning
confidence: 93%
“…That is, it tells us whether the differences are by chance or significant. According to Rayson (2003) cited by Dutra et al (2019), when the result of the LL is greater than 3.8 and smaller than 6.6, there is less than a 5% probability for the result to be by chance, expressed by p>0.05. When the LL result is 6.63, it means that the probability of the result by chance is less than 1% and we can be 99% sure that the difference between the two corpora is not random.…”
Section: Native Corpusmentioning
confidence: 99%
“…Earlier research on LAs also compares the use by native speakers and non-native speakers of English. In the ESL context, Dutra et al (2019) examined the use of LAs of Brazilian ESL learners and English native writers and claimed the differences between them concerning the syntactic position and meaning of the LAs. Whereas in the EFL context, previous studies identified the mismatches of LAs use of native and EFL learners.…”
Section: Introductionmentioning
confidence: 99%